(untitled) (Ameghiniana, 2013)
Abstract. In the southeastern corner of the Isla Grande of Tierra del Fuego, southernmost Argentina, small outcrops representing Late Eocene-Early Oligocene sedimentation in fluvial environments, are referred to the Sloggett Formation. This unit crops out along the shores of Bahía Sloggett, where it is represented by carbonaceous mudstones, sandstones and conglomerates. A new paleofloristic collection of this site, originally reported by Andersson at the beginning of the 20th, was collected and analyzed, revealing the presence of gymnosperm and angiosperm leaves. Conifers are represented by probable Podocarpaceae and the presence of Araucariaceae is confirmed by leaves with preserved anatomy. Angiosperms, although fragmentary, have been grouped in morphotypes, which are referred to the Nothofagaceae, Myrtaceae and Lauraceae. The Sloggett paleoflora is similar in composition to other contemporary floras, described from southern South America and that originated in temperate to cold-temperate and humid forest. Resumen. FLORA PALEÓGENA DE LA FORMACIÓN SLOGGETT, TIERRA DEL FUEGO, ARGENTINA. En el extremo sureste de la Isla Grande de Tierra del Fuego los reducidos afloramientos depositados en un ambiente fluvial durante el Eoceno Tardío-Oligoceno Temprano son conocidos como Formación Sloggett. Dicha unidad aflora a lo largo de la costa de Bahía Sloggett, donde se encuentra representada por pelitas carbonosas, areniscas y conglomerados. Una nueva colección paleoflorística de este sitio, originalmente reportado por Andersson a principios del siglo XX, fue colectada y analizada, reconociendo la presencia de hojas de gimnospermas y angiospermas. Las coníferas están representadas por probables Podocarpaceae junto a hojas con anatomía preservada que indican la presencia de Araucariaceae. Las angiospermas, aunque fragmentarias, han podido ser agrupadas en morfotipos que pueden ser relacionados con Nothofagaceae, Myrtaceae, y Lauraceae. La paleoflora de la Formación Sloggett se asemeja en composición a otras paleofloras contemporáneas de bosques húmedos templados a templados fríos, y que han sido descriptas para dicha región austral.